A new Gd-promoted nickel catalyst for methane conversion to syngas and as an anode functional layer in a solid oxide fuel cell - Wang, W.; Su, C.; Ran, R.; Shao, Zongping (2011)
The effect of lanthanide promoters on a Ni-Al2O3 catalyst for methane partial oxidation, steam reforming and CO2 reforming at 600-850 °C is systematically investigated. The promoters include La2O3, CeO2, Pr2O 3, Sm2O3 and Gd2O3. GdNi-Al2O3 shows comparable catalytic activity to LaNi-Al2O3 and PrNi-Al2O3 but higher activity than CeNi-Al2O3 and SmNi-Al2O 3 for all three reactions. The O2-TPO results show that GdNi-Al2O3 possesses the best coke resistance among those tested. It also displays good stability at 850 °C for 300 h. Raman spectroscopy indicates that the addition of lanthanide promoters can reduce the degree of graphitization of the carbon deposited on Ni-Al2O 3. The GdNi-Al2O3 is further applied as an anode functional layer in solid-oxide fuel cells operating on methane. The cell yields peak power densities of 1068, 996 and 986 mW cm-2 at 850 °C, respectively, for operating on methane-O2, methane-H 2O and methane-CO2 gas mixtures, which is comparable to operating on hydrogen fuel. GdNi-Al2O3 is promising as a highly coking-resistant catalyst layer for solid-oxide fuel cells. © 2010 Elsevier B.V. All rights reserved.